1987
DOI: 10.1007/bf01284461
|View full text |Cite
|
Sign up to set email alerts
|

The[g 9 2/2 ]8+ state in96Zr

Abstract: An 8 + state has been identified at 4390 keY in the doubly semi-magic nucleus 96Zr through the study of angular correlations among the y radiation which is emitted in the B-decay of the 10 s isomer of 96y. This state probably has the configuration ~g~.~ and is populated through a GT decay from ~h~ 8~6member of the [~g^,^(~)vg~,~]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…On the other hand, the (~r g9/2, v~7/2) 1 +, 2 + ..... 8 + multiplet is characterized by (9 = 1 (both quasiparticles obviously are particle-like) and Jff = 0. These predictions are in accordance with the experimental energy pattern [1][2][3][4][5][6][7] in 88,9Oy (Fig. 3) which gives confidence in the results of similar considerations on 96y.…”
Section: Qualitative Considerationssupporting
confidence: 90%
See 2 more Smart Citations
“…On the other hand, the (~r g9/2, v~7/2) 1 +, 2 + ..... 8 + multiplet is characterized by (9 = 1 (both quasiparticles obviously are particle-like) and Jff = 0. These predictions are in accordance with the experimental energy pattern [1][2][3][4][5][6][7] in 88,9Oy (Fig. 3) which gives confidence in the results of similar considerations on 96y.…”
Section: Qualitative Considerationssupporting
confidence: 90%
“…The parabolic rule predicts [1][2][3][4][5][6][7][8] that in 96y the levels 1 § 2 + .... , 8 § lie on a parabola which opens downwards, with the 1 + and 8 + members being shifted down to the bottom of each branch. Furthermore, because of ~#'=0 it follows that E(1 +)<E(8+).…”
Section: Qualitative Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the 8 + , spherical isomer at 1140 keV in 96 Y [57] the (πg 9/2 , νg 7/2 ) 8 + configuration, was assigned [46,52]. The isomer decays by the νg 7/2 → πg 9/2 G-T transition to the 8 + spherical level at 4389.8 keV in 96 Zr having the (πg 2 9/2 ) 8 + configuration [46,63]. In the semimagic 96 Zr, the (πg 2 9/2 ) 8 + , 2-q.p.…”
mentioning
confidence: 99%
“…It has recently been shown that the Z=40 proton and N=56 neutron subshells are almost completely closed at 96Zr [1][2][3] and quadrupole collectivity is restricted to excited multiparticle-multihole configurations which mix weakly with the spherical ground state configuration. It has recently been shown that the Z=40 proton and N=56 neutron subshells are almost completely closed at 96Zr [1][2][3] and quadrupole collectivity is restricted to excited multiparticle-multihole configurations which mix weakly with the spherical ground state configuration.…”
mentioning
confidence: 99%